2021
DOI: 10.1021/acs.nanolett.1c00205
|View full text |Cite
|
Sign up to set email alerts
|

Gigahertz Nano-Optomechanical Resonances in a Dielectric SiC-Membrane Metasurface Array

Abstract: Optically and vibrationally resonant nanophotonic devices are of particular importance for their ability to enhance optomechanical interactions, with applications in nanometrology, sensing, nano-optical control of light, and optomechanics. Here, the optically resonant excitation and detection of gigahertz vibrational modes are demonstrated in a nanoscale metasurface array fabricated on a suspended SiC membrane. With the design of the main optical and vibrational modes to be those of the individual metamolecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For the first time, they reported the anisotropic elastic tensor for single-crystal ITO 29 . Recently, Ajia et al demonstrated a multimodal gigahertz vibrational response corresponding to the mechanical modes of metasurface arrays on a free-standing dielectric membrane 11 . Despite these exciting discoveries, MNOMSs still face some fundamental challenges.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, they reported the anisotropic elastic tensor for single-crystal ITO 29 . Recently, Ajia et al demonstrated a multimodal gigahertz vibrational response corresponding to the mechanical modes of metasurface arrays on a free-standing dielectric membrane 11 . Despite these exciting discoveries, MNOMSs still face some fundamental challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, gold meta-atoms supported by pairs of free-standing silicon nitride strings exhibit individual optomechanical plasmonic resonances . An experimental study of a suspended silicon carbide (SiC) metasurface supporting multimode vibrational resonances was reported . More recently, an experimental demonstration of nonreciprocal transmission and optical bistability at low intensity (∼10 W/cm 2 ) in a free-standing Si 3 N 4 membrane-based metasurface was presented .…”
mentioning
confidence: 99%
“…Breakthroughs have been recently achieved on a “U”-shaped slit array on a silicon carbide (3C-SiC) membrane, which can effectively and coherently drive the cantilever modes in the spectral bands of GHz. 18 The prospects of enhanced photoacoustic effects in dielectric nanoantennas have then to be properly assessed for the realization of subdiffractional phononic devices boosted by non-radiative processes.…”
mentioning
confidence: 99%